2022
DOI: 10.1038/s41598-022-08097-0
|View full text |Cite
|
Sign up to set email alerts
|

Genomic epidemiology of Streptococcus agalactiae ST283 in Southeast Asia

Abstract: Streptococcus agalactiae, also known as Lancefield Group B Streptococcus (GBS), is typically regarded as a neonatal pathogen; however, several studies have shown that the bacteria are capable of causing invasive diseases in non-pregnant adults as well. The majority of documented cases were from Southeast Asian countries, and the most common genotype found was ST283, which is also known to be able to infect fish. This study sequenced 12 GBS ST283 samples collected from adult patients in Thailand. Together with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Taken together, the results of this study highlight the potential of intestinal GBS to cause invasive infection in humans. Although whole genome sequences of isolates in our study, such as E19, PK, B117, B105, and E5, were clustered with other Thai ST283 isolates [ 11 ], cell interaction studies using Caco-2 cell monolayers showed that these isolates were phenotypically different in their magnitudes of invasiveness, their capacity for intracellular survival, and their capability to translocate across polarized Caco-2 cell monolayers. These discrepancies between ST283 isolates could be in part due to the differential expression of genes involved in pathogenicity [ 12 ].…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Taken together, the results of this study highlight the potential of intestinal GBS to cause invasive infection in humans. Although whole genome sequences of isolates in our study, such as E19, PK, B117, B105, and E5, were clustered with other Thai ST283 isolates [ 11 ], cell interaction studies using Caco-2 cell monolayers showed that these isolates were phenotypically different in their magnitudes of invasiveness, their capacity for intracellular survival, and their capability to translocate across polarized Caco-2 cell monolayers. These discrepancies between ST283 isolates could be in part due to the differential expression of genes involved in pathogenicity [ 12 ].…”
Section: Discussionmentioning
confidence: 76%
“…The tendency of this ST to cause invasive disease in patients of various ages, including younger adults, implies that this genotype might have adapted to overcome more potent immune responses of the host. Phylogenetic analysis using whole genome sequences of ST283 recovered from patients of different ages from Southeast Asian countries, including the 12 invasive isolates in this study (see materials and methods), revealed that the genome sequences of isolates from Thailand, Laos, and Singapore are clustered within the same clade [ 11 ], implying that these isolates are genetically closely related.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They usually involve real-time PCR, either "in house" assays, dedicated to a number of PCR devices or molecular platforms. All of them differ in sensitivity and specificity of the results [1,[31][32][33][34][35][36][37][38][39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%